2016
DOI: 10.1038/nm0216-217d
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Snail1-induced partial epithelial-to-mesenchymal transition drives renal fibrosis in mice and can be targeted to reverse established disease.

Abstract: In the version of this article initially published, the labels to the left of the two micrographs in Figure 2c are reversed. Also, in Figure 4g, MKi67, used as a cell proliferation marker, is misspelled. The errors have been corrected in the HTML and PDF versions of the article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…As a strong repressor of E-cadherin gene's transcription, SNAI1 is recognized as an immediate-early gene target of the TGF-β1/SMAD3 pathway and involved in both physiological and pathological EMT. 38 , 39 , 40 , 41 In this study, we observed that TTC36 reduced the expression of SNAI1 and ACTA2 in cultured HK2 cells without TGF-β1 treatment ( Fig. 4 C), suggesting an oppositive role of TTC36 in the regulation of EMT which remains further investigations.…”
Section: Discussionmentioning
confidence: 53%
“…As a strong repressor of E-cadherin gene's transcription, SNAI1 is recognized as an immediate-early gene target of the TGF-β1/SMAD3 pathway and involved in both physiological and pathological EMT. 38 , 39 , 40 , 41 In this study, we observed that TTC36 reduced the expression of SNAI1 and ACTA2 in cultured HK2 cells without TGF-β1 treatment ( Fig. 4 C), suggesting an oppositive role of TTC36 in the regulation of EMT which remains further investigations.…”
Section: Discussionmentioning
confidence: 53%
“…During the development of renal fibrosis, renal epithelial cells undergo a partial EMT and promote production and release of profibrotic growth factors/cytokines, including TGF-␤ 1 . Since Twist1 is the substrate of PRMT1 (1) and activation of Twist is required for the development of EMT in renal tubular cells (8), it is possible that PRMT1 may also be implicated in renal fibrosis through the induction of partial EMT by activation of Twist1. This hypothesis merits further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Damaged tubular epithelial cells secrete large amounts of profibrotic factors, which promote fibrosis formation ( 23 ). In this process, damaged tubular epithelial cells promote expression of key genes such as α-SMA and snail ( 24 , 25 ). In this study, the E-cadherin was down regulated, while the interstitial cell surface marker α-SMA was up-regulated when HK-2 cells were co-cultured with RPMI-8226 cells.…”
Section: Discussionmentioning
confidence: 99%